Diversifikasi Olahan Pepaya menjadi Brownies Kering dan Abon Kering bagi UMKM PRIMA JATI di Desa Rintisan Budaya Jatimulyo, Bantul - Wahidah Mahanani Rahayu; Retnosyari Septiyani; Heni Siswantari; Mufid Salim (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2023)
Jatimulyo Village is one of the villages in Yogyakarta Special Region that will be submitted to Cultural Village establishment. Prima Jati MSME is community organization that processes the local potential of papaya fruit cultivated in Jatimulyo Kapanewon Dlingo Village, Bantul Regency. One of the problems faced is the high level of papaya fruit production with limited processed products and sales. The alternative solution is to diversify papaya into brownies and shredded papaya. The program was conducted through training and mentoring practices for Prima Jati. Both products have been successfully made continuously and have been packaged with plastic standing pouches and jars. There is an increase in community knowledge and understanding of processing papaya fruit into dried products, so as to increase the shelf life of the product. Prima Jati MSMEs have also sold offline at tourist attractions in Jatimulyo and online through social media accounts and marketplaces.